Implementasi FMEA Untuk Perawatan Preventif (Studi Kasus : Fasilitas Usaha Kecil Menengah) - Tiena Gustina Amran; Eldona Lewanskiky (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
East Indonesia focused on Small and Medium- Industry scale businesses (UKM) as one of theway to support society economical growth. UKM Marawey from Seram Island, Ambon, Maluku is facing aproblem on maintaining and preserving the facilities that relates to the venture. Preventive product,process, and facilities maintenance identification are important to assure customer safety and satisfaction.This research focused on analyzing the damage of biodigester machine, egg incubator, gas genset,handcraft machine, and three-wheeled motorcycle. Failure Mode and Effect Analysis (FMEA) researchmethodology and approach was used. The primary step is to identify UKM’s punching operation activities,followed by rating and priority numbering. Preventive measures were given based in Risk Priority Number(RPN) for decisions on each rank of maintenance that were done during the occuring troubles. Theresearch suggests preventive maintenance in 3 categories: Scheduled discard task, scheduled restorationtask, and combination of task. Maintenance cost of machine damage, land, pond, and stall are alsoincluded in the preventive maintenance category. UKM Mawawey preventive maintenance program isexpected to be an example for other UKM in East Indonesia region.Keywords : bio digester, FMEA, maintenance, small medium enterprise